2014
DOI: 10.1016/j.tranon.2014.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Integrin Inhibitor Suppresses Bevacizumab-Induced Glioma Invasion

Abstract: Glioblastoma is known to secrete high levels of vascular endothelial growth factor (VEGF), and clinical studies with bevacizumab, a monoclonal antibody to VEGF, have demonstrated convincing therapeutic benefits in glioblastoma patients. However, its induction of invasive proliferation has also been reported. We examined the effects of treatment with cilengitide, an integrin inhibitor, on bevacizumab-induced invasive changes in glioma. U87ΔEGFR cells were stereotactically injected into the brain of nude mice or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 31 publications
7
44
0
Order By: Relevance
“…Ishida et al (44) reported that an antagonist of integrin αvβ3 and integrin αvβ5 prevented bevacizumab-induced invasion in orthotopic glioma models that express these integrins at high levels. We found that GSC11 cells expressed the POSTN receptors integrin β1 and integrin β3 and that GSC272 cells expressed integrin β1 more highly than integrin β3.…”
Section: Discussionmentioning
confidence: 99%
“…Ishida et al (44) reported that an antagonist of integrin αvβ3 and integrin αvβ5 prevented bevacizumab-induced invasion in orthotopic glioma models that express these integrins at high levels. We found that GSC11 cells expressed the POSTN receptors integrin β1 and integrin β3 and that GSC272 cells expressed integrin β1 more highly than integrin β3.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative reverse transcription-polymerase chain reaction (quantitative RT-PCR) was performed as described previously2047. The expression of GAPDH was used to normalize the amount of cDNA.…”
Section: Methodsmentioning
confidence: 99%
“…CCN1 is known to interact with integrins, such as avb3, a6b1, avb5, and aIIb3, which leads to a variety of biological activities, including cell adhesion, migration, and invasion [10] [39]. We have previously shown that the inhibition of these integrins contributed to anti-glioma effects such as in combination with anti-VEGF therapy and viral therapy [40][41][42]. Recently, integrin avb3/5 inhibitors, such as cilengitide [cyclic RGD peptide (cRGD)], have been focused on the treatment of glioma.…”
Section: Future Directionsmentioning
confidence: 99%